2019
DOI: 10.3390/ijms20246331
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antiarrhythmic, Electrophysiological, and Antioxidative Effects of Melatonin in Ischemia/Reperfusion

Abstract: Melatonin is assumed to confer cardioprotective action via antioxidative properties. We evaluated the association between ventricular tachycardia and/or ventricular fibrillation (VT/VF) incidence, oxidative stress, and myocardial electrophysiological parameters in experimental ischemia/reperfusion under melatonin treatment. Melatonin was given to 28 rats (10 mg/kg/day, orally, for 7 days) and 13 animals received placebo. In the anesthetized animals, coronary occlusion was induced for 5 min followed by reperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…Melatonin receptors are coupled to Kir3.x channels, and melatonin receptor activation shortens the action potential duration [23,47]. However, we recently showed that melatonin-induced changes on myocardial repolarization were associated with melatonin antioxidative properties but not with its antiarrhythmic actions [15,48,49]. Our negative results with nitrotyrosine ( Figure 7) as a marker of nitroxidative stress agree with antioxidant been unrelated to antiarrhythmic effects.…”
Section: Discussionsupporting
confidence: 77%
“…Melatonin receptors are coupled to Kir3.x channels, and melatonin receptor activation shortens the action potential duration [23,47]. However, we recently showed that melatonin-induced changes on myocardial repolarization were associated with melatonin antioxidative properties but not with its antiarrhythmic actions [15,48,49]. Our negative results with nitrotyrosine ( Figure 7) as a marker of nitroxidative stress agree with antioxidant been unrelated to antiarrhythmic effects.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies suggest that targeting arrhythmogenic redox imbalance may provide novel therapeutics to treat or prevent life-threatening arrhythmias and SCD [3,16]. In harmony with it, a large body of evidence of experimental studies point out the benefit of pineal hormone melatonin due to its pleiotropic anti-oxidant and anti-inflammatory actions [11,[21][22][23]. Arrhythmias and abnormalities of Cx43 can be prevented predominantly by mitochondria-targeted antioxidants and the property of melatonin is that it can easily penetrate cells and mitochondria, where it can eliminate the excess of free radicals [24].…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrolled innate immune response promotes a massive inflammatory reaction and causes irreversible tissue damage and mortality. Melatonin is a potent antioxidant and immune regulator that not only suppresses oxidative stress but also controls the innate immune response and promotes the adaptive immune response (15,16). The pineal gland produces and maintains the concentration of melatonin in the blood.…”
Section: Rationale For Melatonin Use In Patients With Covid-19mentioning
confidence: 99%
“…The melatonin produced in the mitochondria is not discharged into the circulation, but is used by the cells that produce it (15). If patients do not generate sufficient amounts of melatonin their health status is likely compromised (16).…”
Section: Rationale For Melatonin Use In Patients With Covid-19mentioning
confidence: 99%